Pelvic chronic pain: more than just endometriosis - Villegas Echeverri, Juan Diego (2016)
Chronic pelvic pain (CPP) is the non-cyclical pain of more than 3 months duration, located in the anatomical area of the pelvis, anterior abdominal wall below the umbilicus, perineum, genital area, lumbosacral region or hip, severe enough to cause functional impairment and / or to seek medical attention. These patients cannot exercise, suffer sleep disorders, cannot enjoy free time, have poor socialization, gait difficulties, poor concentration and a negative impact on their quality of life and sexuality. The general idea that endometriosis is the only cause of chronic pelvic pain is not only wrong, but delays diagnosis and results in improvement rates much lower than expected. A profound change in the way of dealing with patients with CPP is necessary, especially considering endometriosis as the only cause of pelvic pain. Treatment key is to manage CPP as a complex disease. Current evidence shows that diagnosing only one component of this condition (such as endometriosis or pelvic adhesions) and treatment of only that component will probably have no success. Given the current understanding of the neuropathology of chronic pelvic pain, failure of traditional therapy is expected if the condition is not faced with a multidisciplinary and multimodal approach.